Exploring the Types and Categories of Culture in Algerian Official Exam: The Case of Literary and Foreign Languages Stream Texts in English Baccalaureate Exams from 2005 to 2021 (El-Wahat Journal for Research and Studies, 2025)
This descriptive study intends to investigate the types and categories of culture by conducting a content analysis on the texts of 31 foreign languages stream BAC exams from 2005 to 2021. The findings reveal that all analysed texts are designed within a cultural dimension. However, the majority of the texts tend to discuss themes from Big C culture and neglect the small C aspect of culture. Furthermore, the source culture was largely marginalized. Recommendations were provided to make an equilibrated cultural dimension of BAC exam texts.Keywords: Content Analysis, BAC Exam, Culture Types, Culture Categories, Culture and Language